2008
DOI: 10.1016/j.brainres.2007.10.058
|View full text |Cite
|
Sign up to set email alerts
|

In hamsters the D1 receptor antagonist SCH23390 depresses ventilation during hypoxia

Abstract: During exposure of animals to hypoxia, brain and blood dopamine levels increase stimulating dopaminergic receptors which influence the integrated ventilatory response to low oxygen. The purpose of the present study is to test the hypothesis, that in conscious hamsters, systemic antagonism of D 1 receptors would depress their breathing in air and in response to hypoxic and hypercapnic challenges. Nine male hamsters were treated with saline or 0.25 mg/kg SCH-23390 (SCH), a D 1 receptor antagonist that crosses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…The latter finding was also noted in a previous study (Schlenker, 2008). However, the relative increase in ventilation in the hypothyroid hamsters appears not to be metabolically driven, since SCH 23390 had no effect on O 2 consumption or CO 2 production.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The latter finding was also noted in a previous study (Schlenker, 2008). However, the relative increase in ventilation in the hypothyroid hamsters appears not to be metabolically driven, since SCH 23390 had no effect on O 2 consumption or CO 2 production.…”
Section: Discussionsupporting
confidence: 90%
“…However, the relative increase in ventilation in the hypothyroid hamsters appears not to be metabolically driven, since SCH 23390 had no effect on O 2 consumption or CO 2 production. Interestingly in a previous study in hamsters (Schlenker, 2008), a significant effect on body temperature, but not on CO 2 production was noted, but frequency of breathing (but not ventilation) was also lower following SCH 23390 treatment. Whether the difference could have be due to a circannual effect ( Summer: this study, Winter: previous study), is not clear.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It also has been shown that the effects of SCH23390 (at 0.25 mg/kg or higher) on body temperature are evident within a ~3-hour duration (Faunt and Crocker, 1987; Schlenker, 2008). Since our goal was to maintain DA receptor blockade within a 4–5-hour period, our initial treatment was supplemented by an additional half-dose drug administration ~ 2.5 hours after the first injection.…”
Section: Discussionmentioning
confidence: 99%